Political literacy level and political participation rate among Universiti Tunku Abdul Rahman Kampar campus media school students - Ali Imran, Asri (2023)
Political literacy is the ability to comprehend and analyse the political world that surrounds them as well as understanding how governments operate or political processes are formed. Political literacy is crucial in democratic or liberal democratic countries for governments that rely on the citizens to participate in the political process, which in turn requires adequate political literacy and knowledge. In the context of Malaysia, based on recent survey results from past research, it was found that political literacy, especially among the youth between the age of 15 to 30 years old, is severely low. A low level of political literacy among the Malaysian youth poses a significant issue as the youth represents a substantial portion of Malaysian society. In addition, political participation from the youth is necessary for the Malaysian government to understand the youth demographic and formulate efficient and conventional public policies. This project aimed to identify Universiti Tunku Abdul Rahman (UTAR) Kampar Campus media school students’ level of political literacy as well as their rate of political participation. Furthermore, this project also aims to identify the common causes for low political literacy level and political participation. Qualitative research methods were used to gather the data as it allows this topic and issue to be explored further in depth and find any unexpected answers. The research findings suggests that education can strongly impact an individual’s political literacy and in certain circumstances, political participation as well. The respondents in this research showed high political literacy level but low political participation due to political disinterest and negative perception towards Malaysian politics. However, Malaysian youths that do not have the opportunity to pursue tertiary education are likely to have low political literacy but varying rates of political participation which decreases the quality of democracy in Malaysia due to politically ill-informed decision making.